Discovery of a novel natural compound, vitekwangin B, with ANO1 protein reduction properties and anticancer potential - Seo, Yohan; Lee, Sion; Kim, Minuk; Kim, Dongguk; Jeong, Sung Baek; Das, Raju; Sultana, Armin; Park, SeonJu; Nhiem, Nguyen Xuan; Huong, Phan Thi Thanh; Kwon, Oh-Bin; Namkung, Wan; et al. (Frontiers in Pharmacology, 2024)
Background: Prostate cancer and non-small cell lung cancer (NSCLC) present significant challenges in the development of effective therapeutic strategies. Hormone therapies for prostate cancer target androgen receptors and prostate-specific antigen markers. However, treatment options for prostatic small-cell neuroendocrine carcinoma are limited. NSCLC, on the other hand, is primarily treated with epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors but exhibits resistance. This study explored a novel therapeutic approach by investigating the potential anticancer properties of vitekwangin B, a natural compound derived from Vitex trifolia. Methods: Vitekwangin B was chromatographically isolated from the fruits of V. trifolia. ANO1 protein levels in prostate cancer and NSCLC cells were verified and evaluated again after vitekwangin B treatment. Results: Vitekwangin B did not inhibit anoctamin1 (ANO1) channel function but significantly reduced ANO1 protein levels. These results demonstrate that vitekwangin B effectively inhibited cancer cell viability and induced apoptosis in prostate cancer and NSCLC cells. Moreover, it exhibited minimal toxicity to liver cells and did not affect hERG channel activity, making it a promising candidate for further development as an anticancer drug. Conclusion: Vitekwangin B may offer a new direction for cancer therapy by targeting ANO1 protein, potentially improving treatment outcomes in patients with prostate cancer and NSCLC. Further research is needed to explore its full potential and overcome existing drug resistance challenges.